Is the People's Republic of China's current slowdown a cyclical downturn or a long-term trend? A productivity-based analysis - Chong-En Bai; Qiong Zhang (Asian Development Bank Institute (ADBI), 2017)
Whether the People's Republic of China's (PRC) economic slowdown since the 2008 financial crisis is a cyclical downturn or a long-run trend has important policy implications. Based on provincial panel data, this article identifies the determinants of productivity and uses counter-factual analysis to decompose the causes of the PRC's post-crisis slowdown. It finds that economic openness has a significantly positive impact on the technical efficiency of production, whereas the income level has a significantly negative effect. Second, a significantly negative correlation is observed between the stock of inventory and productivity, while the opposite is observed between employment involvement rate and productivity. Third, government size and investment rates both have significantly negative effects on productivity. Lastly, the diminishing late-mover advantage and the growth in investment rate are both major contributors to the current decline in the PRC's productivity. Although the stimulus-induced investment surge has effectively offset the negative effects of the crisis on the PRC's growth, it is not conducive to the growth of productivity and consumption. The current economic slowdown does not seem to be a cyclical downturn. Indeed, further reforms are needed to stabilize the PRC's growth.
Keywords: O47; E20; 330; productivity; technical efficiency; utilization efficiency; allocative efficiency; counter-factual analysis